2006
DOI: 10.1007/s10765-006-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

Corresponding-States Modeling of the Speed of Sound of Long-Chain Hydrocarbons

Abstract: Models based on the corresponding-states principle have been extensively used for several equilibrium and transport properties of different pure and mixed fluids. Some limitations, however, have been encountered with regard to its application to long chain or polar molecules. Following previous studies, where it was shown that the corresponding-states principle could be used to predict thermophysical properties such as vapor-liquid interfacial tension, vapor pressure, liquid density, viscosity, and thermal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 68 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Knowledge of the physical and chemical properties of ILs is essentially important to optimize the use of ILs and design the desirable ILs. The speed of sound, u , is an important thermodynamic property that can be experimentally determined with great precision over a broad range of temperature and pressure, and it can be related with other thermodynamic properties such as density, heat capacity, thermal conductivity, and isentropic and isothermal compressibilities, which are essential for the accurate design and optimization of several industrial processes. The speed of sound is related to density, ρ and isentropic compressibility, κ S through Newton‐Laplace's equation κS=1ρu2 …”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the physical and chemical properties of ILs is essentially important to optimize the use of ILs and design the desirable ILs. The speed of sound, u , is an important thermodynamic property that can be experimentally determined with great precision over a broad range of temperature and pressure, and it can be related with other thermodynamic properties such as density, heat capacity, thermal conductivity, and isentropic and isothermal compressibilities, which are essential for the accurate design and optimization of several industrial processes. The speed of sound is related to density, ρ and isentropic compressibility, κ S through Newton‐Laplace's equation κS=1ρu2 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a rational function, which correlates 1/ c 2 as a function of the pressure and temperature by considering nine adjustable parameters, was used to correlate the experimental speeds of sound in liquid MeC10:0, MeC12:0, and MeC14:0, respectively, which is shown as follows: in which in eq , and the adjustable parameters A 0 – A 3 , B , C , D , E 1 , and F were listed in Table . This function was initially proposed by Daridon et al and improved by Queimada et al, which has been demonstrated to provide an adequate correlation of speed of sound data for n -alkanes ranging from ethane up to n -hexatriacontane with an average deviation of less than 1%. , …”
Section: Resultsmentioning
confidence: 99%
“…In the literature surveyed on the bulk modulus of compressibility there are a number of models used by different authors to estimate the speed of sound in biodiesel. Nevertheless, only two models are commonly used an Example of these authors who have conducted experimental work include [505][506][507][508][509].…”
Section: The Bulk Modulus Of Compressibilitymentioning
confidence: 99%